2011
DOI: 10.5539/ijbm.v7n1p126
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction among Academic Staff: A Comparative Analysis between Public and Private Sector Universities of Punjab, Pakistan

Abstract: Purpose-The purpose of this study was to investigate the relationship between various facets of job satisfaction among university academicians in Punjab Province, Pakistan, and how these differences affect overall job satisfaction of academicians in selected universities of Province Punjab.Design/ methodology/approach-The Population for this study comprised of academicians working in universities chartered by Higher Education Commission (HEC) of Pakistan. A total of 150 questionnaires were sent to potential re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 31 publications
5
60
0
7
Order By: Relevance
“…The table further shows academicians who work for private universities are more satisfied than those who work for governmental universities. In this respect, Khalid et al (2012) found academicians in private universities are more satisfied with their pay, supervision, and promotional opportunities than academicians in public universities. The result is explained on the grounds that most of the academic staff in private universities are non-Kuwaitis.…”
Section: Level Of Job Satisfaction and Respondents' Characteristics Amentioning
confidence: 95%
See 2 more Smart Citations
“…The table further shows academicians who work for private universities are more satisfied than those who work for governmental universities. In this respect, Khalid et al (2012) found academicians in private universities are more satisfied with their pay, supervision, and promotional opportunities than academicians in public universities. The result is explained on the grounds that most of the academic staff in private universities are non-Kuwaitis.…”
Section: Level Of Job Satisfaction and Respondents' Characteristics Amentioning
confidence: 95%
“…Based on the above theories, several studies have developed to identify factors behind job satisfaction among academic staff. They were undertaken in various places (see for example, UK: Oshagbemi, 1996, Ward and Sloane 2000, Stevens 2005; Canada: Leckie and Brett 1997; Turkey: Kusku 2003, Bayram et al 2010, Toker 2011, Saygi et al 2011 Khalid et al 2012, Mehmood et al 2012, Sohail and Delin 2013, Syed and Ahmedani 2013; India. Shamra and Manani 2012; Jordan: Abushaira 2012; Vietnam: Wang et al 2014;Shin and Jung 2014 1 ).…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, unfair or lack of promotion opportunities do affect particularly young employees who are looking for more work experiences from various institutions. For example, a study on the effect of promotion opportunities in influencing job satisfaction among academics in higher public institutions in New Zealand by Khalid et al (2011) indicates that academicians in private universities were more satisfied with their promotional opportunities, pay and supervision than the academicians of public university.…”
Section: Promotion and Employee Satisfactionmentioning
confidence: 99%
“…However, Griffee (2012) mentioned that a ty pical guideline is that 0.3 at the threshold, 0.5 or higher is adequate, and 0.7 or higher is high. George and Mallery (2003) provide more detailed categories of reliability va lues as rules of thumb (i.e., >0.9 "Excellent", >0.8 "Good", >0.7 "Acceptable", >0.6 "Questionable", >0.5 "Poor", while <0.5 "Unacceptable") (as cited in Khalid et al 2012). From another standpoint, there are works in the literatures recom mends using specific values of reliability according to the nature of the study since the reliability relies on a large ex tent on the use that is to be made of the results.…”
Section: Reliability: Your Way To Go Ahead Confidentlymentioning
confidence: 99%